Teaching Reading through “The Power of Two” Strategy for Senior High School Students - Rahmah Ulfa Andini; Ratmanida Ratmanida (Journal of English Language Teaching, 2019)
Reading is an important skill that is needed to get information from written text. In reading skill, students not only  have to read but they have to comprehend the text in order to get the meaning from the text that they have been read.  Although, many students still have difficulties in comprehending the text and low motivation in reading. It caused that there is a tendency the teacher does not use teaching strategy appropriately. That is why this paper is conducted in order to explain how to use “The Power of Two” strategy in teaching reading for senior high school students’. “The Power of Two” strategy is conducted to help students in comprehending the text by work in pairs so that students can change their mind with each other. This strategy will facilitate students to figure out their problems in reading. It also can make students enjoy and relax in reading process. Thus, students can improve their reading skill ability.